USAHA PERLUASAN KESEMPATAN KERJA BAGI ANGKATAN KERJA MELALUI PELATIHAN PADA BIDANG TEKNISI KOMPUTER - Burham Isnanto; Ari Amir Alkodri; Seno Hadi Saputro; Ferry Bakti Atmaja (Jurnal Pengabdian Masyarakat Polmanbabel, 2021)
Abstract Indonesia faces challenges in the future to make the demographic bonus as a driving force for the economy or will it just be a burden on the State. To improve human resources competences and minimize the unemployment rate, one of the efforts undertaken is to undertake a vocational training program through cooperation with partners in each city. ISB Atma Luhur as a partner in collaboration with BPJAMSOSTEK held training in the field of computer technicians. This training is specifically intended for BP Jamsostek participants who are no longer working as well as several other requirements. Activities carried out include providing entrepreneurship and computer materials, home PC assembly practices, discussion of assembly problems, Windows installation practices, drivers and supporting software, and discussion of OS problems. The end result of this training is 15 trainees ability increase and given certificates so thay they can use them as training proof when they looking for work.